A direct high-throughput in Cell-ELISA for measuring infectivity of cytopathic and non-cytopathic bovine viral diarrhoea virus strains applied to the assessment of antiviral activity - Quintana, Maria Eugenia; Barone, Lucas; Forlenza, María Belén; Trotta, Myrian Vanesa; Turco, Cecilia; Mansilla, Florencia Celeste; Cardoso, Nancy Patricia; Capozzo, Alejandra Victoria (Elsevier, 2019)
Low-cost high-throughput methods applicable to any virus strain are required for screening antiviral compounds against multiple field strains. Colorimetric cell-viability assays are used for this purpose as long as the viruses are cytopathic (CP) in cell culture. However, bovine viral diarrhoea virus (BVDV) strains circulating in the field are mostly non-cytopathic (NCP). An In Cell-ELISA aimed to measure viral infectivity by detecting a conserved protein produced during viral replication (non-structural protein 3, “NS3”) was developed. The ELISA is performed without harvesting the cells, directly on the 96-wells culture plate. NS3 In Cell-ELISA was tested for its ability to assess BVDV-specific antiviral activity of recombinant bovine type I and III IFNs. Results correlated to those measured by qRT-PCR and virus titration. NS3 In Cell-ELISA was also efficient in estimating the IC50 of two compounds with different antiviral activity. Estimation of the 50% inhibition dose of each IFN using six BVDV strains of different biotype and genotype showed that CP strains were more susceptible to both IFNs than NCP, while type 2 NCP viruses were more sensitive to IFN-I. The In Cell-ELISA format using a detector antibody against a conserved non-structural protein can be potentially applied to accurately measure infectivity of any viral strain.